A near‐complete genome sequence of mungbean (Vigna radiata L.) provides key insights into the modern breeding program - Jungmin Ha (Wiley, 2021)
Abstract Mungbean (Vigna radiata L.), a fast‐growing legume species, is an important source of carbohydrates and proteins in developing countries of Asia. Here, we constructed a near‐complete genome sequence of mungbean with a scaffold N50 value of 5.2 Mb and only a 0.4% gap, with a total scaffold size of 475 Mb. We identified several misassembled pseudomolecules (Chr03, Chr04, Chr05, and Chr08) in the previous draft assembly; Chr03, Chr04, and Chr08 were assembled into one chromosome, and Chr05 was broken into two chromosomes in the improved reference genome assembly, thus providing more accurate linkage information to breeders. Additionally, using an ultra‐high‐resolution linkage map constructed based on resequencing data, we identified several quantitative trait loci (QTLs) and the underlying candidate genes affecting synchronous pod maturity (SPM). Mungbean homologs of two soybean ([Glycine max (L.) Merr.] flowering genes, E3 (phytochrome A) and J (early flowering 3), were identified as candidate genes for the QTLs, and the candidate genes for plant height, node number, and SPM showed critical nucleotide substitutions between the reference cultivar and other genotypes (landraces and wild accessions). Based on the analysis of genetic diversity among 276 accessions collected from 23 countries, we identified 36 selective sweep regions and observed that the overall genetic diversity of cultivars decreased to 30% of that in wild accessions postdomestication. The near‐complete genome sequence of mungbean represents an important resource for genome‐assisted improvement in the mungbean breeding program.